Work or family…? Huge conflict in working population: a cross sectional study in a city in Karnataka - K., Ratnaprabha G.; P., Sindhu; Kumar, Aswin; Kengnal, Prakash R.; M. S., Ashok kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Work and family are the most important responsibilities of an adult. The last two decades have been marked by striking changes in the world of work and nature of the family. Work schedules, work orientation, marriage, children and spouse employment patterns may all produce pressures to effectively exhibit ones work role or the family role, which are interdependent. The objectives of the study were to assess work family conflict (WFC) among the working population in a city in Karnataka, and its determinants. Methods: A community based cross sectional study was carried out during August-September 2015 among 400 adult working population of Davangere city, working in different sectors (hospitals, schools, colleges, banks and police department). A pretested structured self-administered questionnaire consisting of socio-demographic details, Carlson’s Work-Family Conflict Scale was used. Data was analyzed using SPSS 10 for frequencies, Chi square test, student’s T test and ANOVA. Results: Out of 400 study participants, 62% were men. Mean scores of work to family conflict was 27.28±5.68 and that of family to work conflict was 25.37±5.61. Time based work to family conflict was more compared to strain and behaviour based. Conflict scores were higher for females, >45 years age, employees who had children, especially child under 5 years of age. WFC was found to be highest among doctors, police and nurses. Conclusions: Work to family conflict was higher than family to work conflict, especially time based.